Synthesis and Characterization of Co+2,Ni+2,Cu+2 ,Zn+2 and Hg+2 Complexes With 1,1,2,2-Tetrakis (Sodium Thiolactate) Ethylene - Buttrus, N. H. (Science Journal of University of Zakho, 2013)
The new ligand 1,1,2,2-tetrakis(sodium thiolactate) ethylene, has been prepared from the reaction of disodium salt of thiolactic acid and tetrachloroethylene in (4:1) molar ratio. Di and tetranuclear complexes were obtained by direct reaction of the above ligand with Co+2,Ni+2,Cu+2 , Zn+2 and Hg+2 metal ion in (1:2) and (1:4) ligand to metal molar ratio. The prepared complexes were characterized by elemental analysis, spectral studies (FTIR.,UV/vis), magnetic measurements, conductivity measurements. Electronic spectra and magnetic moment values indicate the presence of tetrahedral geometric around the metal ions.